Identification of Drug Related Problems (DRPs) Based on Drug and Dosage Selection in Type 2 Diabetes Mellitus Patients - Wijaya, Dhani; Rahmadanita, Fathia Faza; Atmaja, Ria Ramadhani Dwi; Syarifuddin, Sadli; Mutiah, Roihatul; Habibah, Atiqoh Nur; Nafisah, Fika Sayyidatun (Pharmacology and Clinical Pharmacy Research, 2025)
Pharmacological therapy for type 2 diabetes mellitus involves more than one type of drug, this increases the potential for Drug Associated Problems (DRPs) in terms of selecting the type and dose of the drug. This study aimed to determine the treatment profile and identify the occurrence of DRPs based on drug selection and dosage in patients with type 2 diabetes mellitus. This descriptive observational study was conducted in October 2022 in the medical record room of one general hospital in Batu, East Java. The study sample was obtained by total sampling using 36 medical records of inpatients with type 2 diabetes mellitus without complications. Identification of DRPs based on The Pharmaceutical Care Network Europe (PCNE) V.9.1 guidelines. The results showed that glimepiride (6.45%), insulin (16.13%), a combination of metformin and glimepiride (3.23%), a combination of metformin and insulin (3.23%), and basal-bolus insulin (67.74%) were antidiabetic drugs used by patients. Based on the drug selection, 17 patients were identified as having DRPs where the use of drugs without indication (38.89%) was the most common case. Meanwhile, DRPs based on dose selection were found in 6 patients with 13.89% of cases being too high a drug dose. Based on this study, it can be concluded that there are cases of DRPs based on drug selection and dosage in patients with type 2 diabetes mellitus so improved pharmaceutical services are needed to address this to improve patient safety.